INCREASE MSMEs CAPITAL IN COVID 19 PANDEMIC THROUGH CASH WAQF - Faisal Faisal (Proceeding International Seminar of Islamic Studies, 2021)
The spread of covid19 in our country has a very serious impact on the economic life of the people, especially traders who are classified as UMKM. During the pandemic, UMKM traders issued capital to sell but buyers were reduced. As a result they lack capital to resell. Many of them had to stop trading due to reduced buyers. This leads to a decrease in their income, even though they have a lot of needs. This is a problem for them. In order to help UMKM traders who have experienced a lack of capital during pandemic period, it is necessary to increase the capital of UMKM traders in the covid 19 pandemic through the empowerment of cash waqf.   The research is normative juridical research. The data sources in this research is secondary data.The technique to collecting data is documentation study. Based on the research discovered that waqf has social functions that act as a means and capital for the improvement of the means of people. The increase in UMKM capital in the pandemic era can be done by providing assistance in the form of capital for UMKM traders, especially those who reduce their income as a result of the covid19 outbreak. With the help of capital through cash waqf it is hoped that UMKM traders can resell or can increase their capital. With waqf cash, then, UMKM traders will be helped and able to sell for the fulfillment of their family's life needs.Keywords: Capital, MSMEs, Cash